Revealing the significant shortcomings in the learning environment at the three largest medical schools in Syria: what’s next? - Ghaith Alfakhry; Ahmad Naeem; M. Bader AboHajar; Aisha Alfakhry; Abdul Fattah Mohandes; Iyad Ali; Ebrahim Makhoul; Nadeem Ahmed; M. Mhdy Abla; Khaled Alhomsi; Issam Jamous (BMC Medical Education, 2023)
Abstract Background Medical education in Syria still adopts a traditional, teacher-centered curriculum to this day. These elements imply the existence of issues in the learning environment (LE). This study aims to provide the first evaluation of the LE at the largest medical schools in Syria using the DREEM inventory. Methods The three largest medical schools in Syria are the ones at Damascus University (DU), University of Aleppo (AU), Tishreen University (TU). The Arabic version of the DREEM questionnaire was used. Students across all years of study except year 1 were approached. Both paper-based and electronic surveys were conducted. Results A total of 1774 questionnaire forms were completed (DU:941, AU:533, TU: 300). The overall DREEM score at DU, AU, and TU were 100.8 ± 28.7, 101.3 ± 31.7, and 97.8 ± 35.7 respectively with no significant difference (P = 0.254) between the three universities. DREEM subscales concerning Learning, Atmosphere, Academic Self-perception and Social Self-perception had a low score across all universities. Clinical-stage students reported significantly lower perception (P  ≤ 0.001) of the LE in comparison to their pre-clinical counterparts across all subscales. Conclusions The findings of this study highlight the significant shortcomings of the medical LE in Syria. If not addressed properly, the academic, clinical, and professional competence of the healthcare workforce will continue to deteriorate. Moreover, the negative LE might be a predisposing factor for medical students’ exodus. The Syrian medical education system requires leaders who are willing to defy the status quo to achieve a true educational transformation.